Differentiation Development Strategy at University of HKBP Nommensen Pematangsiantar Through Swot Method Strength,Weaknesses,Oppurtunities and Threats - Leo Fernando SIMATUPANG; Tumpal Manahara SIAHAAN; Bintang Marlyn MARBUN (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to analyze the achievement of product service differentiation and develop a differentiation development strategy at HKBP Nommensen University, Pematangsiantar. The urgency of the research is that there has been a decline in productivity over the past 4 years (2021-2024) as seen from the failure to achieve the target number of new student registrations, namely 1200 new students per year. Therefore, the researcher took the indicator of developing an expansion strategy through the SWOT variable aspect (strengths, weaknesses, opportunities and threats) as a reference in improving service products and productivity, especially increasing new student admissions. The intended output in the study is the publication of a sinta 4 (four) accredited journal. This study uses a qualitative-descriptive approach. The aim is to provide a complete picture, summarize various conditions, situations from various data that have been collected at HKBP Nommensen University, Pematangsiantar. The research subjects were selected by purposive sampling. The data collection techniques used were observation, interviews, and documentation.